Bacillus cereus s-EPS as a dual bio-functional corrosion and scale inhibitor in artificial seawater. (1st December 2019) - Li, Shunling; Qu, Qing; Li, Lei; Xia, Ke; Li, Yan; Zhu, Tingting
Abstract: In this study, soluble extracellular polymeric substances (s-EPS) secreted by Bacillus cereus ( B. cereus ) were studied as a novel, dual bio-functional corrosion and scale inhibiting material, in artificial seawater. Static tests showed that the scale inhibition efficiency (SI%) was close to 87.60% for CaCO3 at the concentration of 80 mg/L s-EPS. Electrochemical technique results showed that s-EPS inhibition efficiencies, in relation to 316L stainless steel (SS), and at the concentration of 40 mg/L, reached 91.05% at 10 d and 91.16% at 30 d, respectively. The high anti-scale and anti-corrosion performance of s-EPS was related to their chelating, adsorption, and biomineralization abilities. s-EPS integrated with metal ions on the SS surface, resulting in formation of a thin but dense biomineralized film, which exhibited lasting corrosion resistance. Meanwhile, s-EPS controlled the kinetic pathway of CaCO3 biomineralized nucleation and crystal growth, which inhibited CaCO3 crystal precipitation. This finding suggests that B. cereus s-EPS may offer a green, sustainable, and economic strategy for anti-corrosion and anti-scale application in industry. Graphical abstract: Image 1 Highlights: B. cereus s-EPS as dual bio-functional corrosion and scale inhibitor was studied. The scale inhibition efficiency of B. cereus s-EPS on CaCO3 was achieved 87.60%. The highest corrosion inhibition efficiency of B. cereus s-EPS on stainless steel was 91.16%. Lasting anticorrosion of s-EPS was ascribed to biomineralized film formation. Anti-scale of s-EPS was related to the effect of functional group of s-EPS on the mineralization of CaCO3 .